INTENSITY OF SECONDHAND SMOKE EXPOSURE IS ASSOCIATED WITH SUBCLINICAL ELEVATION OF SERUM ALT LEVELS IN HEALTHY YOUNG ADULTS - Kurnia, Dimas Ardi; Yulia Ratna Dewi; Yulita Maulani (Tahta Media Group, 2025)
Background: Secondhand smoke exposure contains various toxic compounds that may affect liver function even in young, apparently healthy individuals. Evidence regarding the impact of exposure intensity on liver enzyme activity remains limited. Objective: This study aimed to analyze the association between secondhand smoke exposure intensity and serum alanine aminotransferase (ALT/SGPT) levels among university students. Methods: A cross-sectional study was conducted among 99 university students selected using purposive sampling. Exposure intensity was quantified using a structured questionnaire based on frequency and duration of exposure. Serum ALT levels were measured using an enzymatic method with an automated chemistry analyzer. Data were analyzed using Spearman’s correlation test. Results: A significant positive correlation was observed between secondhand smoke exposure intensity and serum ALT levels (r = 0.293, p = 0.003). Although most ALT values remained within normal reference ranges, higher exposure intensity was associated with a gradual increase in ALT levels. Conclusion: Increased intensity of secondhand smoke exposure is associated with subclinical elevation of serum ALT levels in healthy young adults. These findings highlight the importance of minimizing passive smoke exposure even in non-smoking populations.